Smoking: Habit repercusion on the breastfeeding establishment and maintenance - Susana Iglesias Casás (Fundación para el Desarrollo de la Enfermería, 2008)
Passive smoking might produce in newborns a higher risk of sudden death and respiratory diseases, having breastfeeding a protective effect on these complications.This study research the association between smoking on women, the kind of lactation that she determines and the total duration of breastfeeding.The study population were all the women who had just given birth in two hospitals from the province of Pontevedra, between August and September 2005, whom were interviewed when discharged from hospital. Those who breastfeeded were phone interviewed after 3, 6 and 12 months.77.6% of non-smoking women choose exclusively breastfeeding when discharged from hospital, a 30.6% of then followed after 6 months and they have a breastfeeding average time of 5.7 months (SD = 4.1).Smoking before pregnancy influences negatively on the maintaining of exclusively breastfeeding after 6 months (p = 0.02).Smoking during pregnancy associates to a lower exclusively breastfeeding initiation (p = 0.02) and to a lower prevalence after 3 and 6 months (p = 0.004 and p= 0.02 respectively). Children of smoking women have not even the harmful passive smoking effects, but also the lack of protective effect of breastfeeding: this is initiated less and for a lower time.As during pregnancy and breastfeeding women have more contact to the sanitary professionals, we should insist on the fact that smoking is not a breastfeeding contraindication.